2022
DOI: 10.1038/s41598-022-21159-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrated radiogenomics analyses allow for subtype classification and improved outcome prognosis of patients with locally advanced HNSCC

Abstract: Patients with locally advanced head and neck squamous cell carcinoma (HNSCC) may benefit from personalised treatment, requiring biomarkers that characterize the tumour and predict treatment response. We integrate pre-treatment CT radiomics and whole-transcriptome data from a multicentre retrospective cohort of 206 patients with locally advanced HNSCC treated with primary radiochemotherapy to classify tumour molecular subtypes based on radiomics, develop surrogate radiomics signatures for gene-based signatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In the ongoing pursuit of biomarker development through the lens of radiogenomics, Meneghetti et al. [56] organized molecular subtypes and employed 10 distinct representative CT scans to categorize 206 patients with untreated HNSCC. The objective of this categorization was to train machine learning algorithms to recognize these distinct features, facilitating subsequent assessments of the prognostic value of locoregional control in HNSCC model validation.…”
Section: Addition Of Biologic Approaches In Radiomics For Hnc Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In the ongoing pursuit of biomarker development through the lens of radiogenomics, Meneghetti et al. [56] organized molecular subtypes and employed 10 distinct representative CT scans to categorize 206 patients with untreated HNSCC. The objective of this categorization was to train machine learning algorithms to recognize these distinct features, facilitating subsequent assessments of the prognostic value of locoregional control in HNSCC model validation.…”
Section: Addition Of Biologic Approaches In Radiomics For Hnc Diagnosismentioning
confidence: 99%
“…Meneghetti et al. [56] improved both risk stratification and model calibration by combining CT‐based radiomics with transcriptome metagenes. They found that higher hedgehog metagene values were associated with increased recurrence risk, whereas E2F metagenes showed the opposite trend.…”
Section: Risk Stratification and Prognostic Biomarkersmentioning
confidence: 99%
“…They found out that integrative multiomics (radiomics, genomics, transcriptomics, and proteomics) data have the best OS prediction power followed by radiomics + omics, and single omics. OS analysis via multiomics data and advanced ML modeling is rapidly advancing in other cancer types, such as HNSCC, 28 pancreatic cancer, 29 liver and breast cancer, 25 etc.…”
Section: Applications Of Multiomicsmentioning
confidence: 99%
“…Rabasco et al conducted a study on the molecular subtypes of locally advanced HNSCC using radiomics. They successfully improved the prognostic value of localized regional control by combining radiomic and transcriptomic features [ 121 ]. Huang et al employed CT radiomics to differentiate between various molecular subtypes of HNSCC, including RNA-defined HPV status, five DNA methylation isoforms, four gene expression isoforms, and five somatic gene mutations.…”
Section: Multiomics Of Radiomics Genomics and Pathomics Combined To E...mentioning
confidence: 99%